Filipino-Chinese national identity, social values and perception towards Filipinos and the Philippines. - Dela Cruz, Mary Grace G.; Espanola, Bambi Rose. (2013.)
This study investigated Filipino-Chinese national identity, social values and perception towards Filipinos and the Philippines. The respondents were 35 male and 26 female students from Iloilo Sun Yat Sen High School who have Chinese descent and with age and years of residency in the Philippines ranging from 12-18 years. this study utilized three survey questionnaires: National Identity Questionnaire, Social Values Scale, and Perception towards Filipinos and the Philippine Scale. Results showed that majority of the respondents have already integrated in the Philippines. They have high level of Filipino national identity, high level of Filipino social values and positive perception towards Filipinos and the Philippines. Also, the respondents' national identity was significantly correlated to their social values and perception towards filipinos and the Philippines
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Filipino-Chinese National Identity